Transversus Abdominis Plane Block to Ameliorate Postoperative Pain Outcomes After Laparoscopic Surgery: A Meta-Analysis of Randomized Controlled Trials - De Oliveira, Gildasio S.; Castro-Alves, Lucas Jorge; Nader, Autoun; Kendall, Mark C.; McCarthy, Robert J. (Anesthesia and analgesia, 2014)
Transversus abdominis plane (TAP) block has been used as a multimodal strategy to optimize postoperative pain outcomes; however, it remains unclear which type of surgical procedures can benefit from the administration of a TAP block. Several studies have examined the effect of the TAP block on postoperative pain outcomes after laparoscopic surgical procedures and generated conflicting results. Our main objective in the current investigation was to evaluate the effect of TAP block on postoperative analgesia outcomes for laparoscopic surgical procedures. A search was performed to identify randomized controlled trials that evaluated the effects of the TAP block compared with an inactive group (placebo or "no treatment") on postoperative pain outcomes in laparoscopic surgical procedures. Primary outcomes included early (0-4 hours) and late (24 hours) postoperative pain at rest and on movement and postoperative opioid consumption (up to 24 hours). Meta-analysis was performed using a random-effects model. Publication bias was evaluated by examining the presence of asymmetric funnel plots using Egger regression test. Meta-regression analysis was performed to establish an association between the local anesthetic dose and the evaluated outcomes. Ten randomized clinical trials with 633 subjects were included in the analysis. The weighted mean difference (99% confidence interval) of the combined effects favored TAP block over control for pain at rest (≤4 hours, -2.41 [-3.6 to -1.16]) and (at 24 hours, -1.33 [-2.19 to -0.48]) (0-10 numerical scale). Postoperative opioid consumption was decreased in the TAP block group compared with control, weighted mean difference (99% confidence interval) of -5.74 (-8.48 to -2.99) mg morphine IV equivalents. Publication bias was not present in any of the analysis. Preoperative TAP block administration resulted in greater effects on early pain and opioid consumption compared with postoperative administration. Meta-regression analysis revealed an association between local anesthetic dose and the TAP block effect on late pain at rest and postoperative opioid consumption. None of the studies reported symptoms of local anesthetic toxicity. TAP block is an effective strategy to improve early and late pain at rest and to reduce opioid consumption after laparoscopic surgical procedures. In contrast, the TAP block was not superior compared with control to reduce early and late pain during movement. Preoperative administration of a TAP block seems to result in greater effects on postoperative pain outcomes. We also detected a local anesthetic dose response on late pain and postoperative opioid consumption.